Integrated transcriptomic analysis identifies coordinated responses to nitrogen and phosphate deficiency in rice - Wang, Fei; Wang, Yan; Ying, Luying; Lu, Hong; Liu, Yijian; Liu, Yu; Xu, Jiming; Wu, Yunrong; Mo, Xiaorong; Wu, Zhongchang; Mao, Chuanzao (Frontiers in Plant Science, 2023)
Nitrogen (N) and phosphorus (P) are two primary components of fertilizers for crop production. Coordinated acquisition and utilization of N and P are crucial for plants to achieve nutrient balance and optimal growth in a changing rhizospheric nutrient environment. However, little is known about how N and P signaling pathways are integrated. We performed transcriptomic analyses and physiological experiments to explore gene expression profiles and physiological homeostasis in the response of rice (Oryza sativa) to N and P deficiency. We revealed that N and P shortage inhibit rice growth and uptake of other nutrients. Gene Ontology (GO) analysis of differentially expressed genes (DEGs) suggested that N and Pi deficiency stimulate specific different physiological reactions and also some same physiological processes in rice. We established the transcriptional regulatory network between N and P signaling pathways based on all DEGs. We determined that the transcript levels of 763 core genes changed under both N or P starvation conditions. Among these core genes, we focused on the transcription factor gene NITRATE-INDUCIBLE, GARP-TYPE TRANSCRIPTIONAL REPRESSOR 1 (NIGT1) and show that its encoded protein is a positive regulator of P homeostasis and a negative regulator of N acquisition in rice. NIGT1 promoted Pi uptake but inhibited N absorption, induced the expression of Pi responsive genes PT2 and SPX1 and repressed the N responsive genes NLP1 and NRT2.1. These results provide new clues about the mechanisms underlying the interaction between plant N and P starvation responses.